TRANSFORMATIVE ISLAMIC RELIGIOUS EDUCATION PEDAGOGY: INTEGRATING AL-ISHLAH WA AL-TAGHYIR VALUES TO ADDRESS ACADEMIC BURNOUT IN HIGHER EDUCATION - Budiyanti, Nurti; Aziz, Asep Abdul; Fajar Islamy, M. Rindu; Suhada, Arie Noviana (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to design a transformative Islamic Religious Education (PAI) pedagogical model integrating Al-Ishlah (self-improvement) and Al-Taghyir (fundamental transformation) values to address the academic burnout phenomenon among university students in Indonesia. A qualitative descriptive case-study design situated within a Design-Based Research (DBR) framework was employed. Data were collected through in-depth semi-structured interviews with PAI lecturers and students (n = 12; three lecturers and nine students, selected via purposive sampling at Universitas Pendidikan Indonesia), six participatory classroom observations, and documentary analysis of lesson plans (RPP), student spiritual journals, and institutional reports. Data were analyzed using an interactive analysis model (reduction, display, conclusion drawing) combined with thematic analysis to identify religious coping patterns. Approximately 59% of students exhibited moderate burnout and 24% high burnout, with emotional exhaustion and cynicism as the dominant dimensions. Al-Ishlah manifested through three domains: a self-improvement framework, an affective pedagogical approach grounded in rahmah (compassion), rifq (gentleness), and ihtimam (attentiveness), and value internalization through structured muhasabah (self-introspection) via spiritual journaling. Al-Taghyir operated through four strategies: establishing transformative learning objectives, structured religious habituation, progressive responsibility assignment, and strengthening transcendental motivation. A Critical-Integrative Pedagogy Model integrating both values is proposed as a holistic framework with demonstrated potential to support stress reduction and academic resilience. This study is limited to the PAI context in one higher education institution; empirical validation through quasi-experimental designs is required to establish causal effectiveness. Findings carry practical implications for Islamic curriculum development, PAI lecturer training, and institutional mental-health policy in Indonesian higher education. This study offers conceptual novelty by operationalizing the Islamic theological-philosophical framework of Al-Ishlah wa Al-Taghyir as primary pedagogical organizing principles rather than supplementary coping strategies to address academic burnout, providing an Islamic epistemological alternative to Western psychological interventions that currently dominate the literature.